Resistance to Herbicides in the Model Organisms Saccharomyces cerevisiae and Arabidopsis thaliana: the Involvement of Multidrug Resistance Transporters - Cabrito, Tânia; Remy, Estelle; Teixeira, Miguel; Duque, Paula; Sá-correia, Isabel (IntechOpen, 2011)
None